Modeling and Simulation of DC Glow Discharges in the AlGaSb coupled Ar/H2 Hybrid Micro Plasma System - Ongun, Erhan; Utaş, Selçuk; Kurt, Hilal; Hançerlioğulları, Aybaba (Politeknik Dergisi, 2025)
Several studies have been reported on the theoretical and experimental investigation of gas discharge - semiconductor micro plasma systems (GDSµPS). In this study, a two-dimensional fluid model of a micro plasma in a square direct-current (DC) glow-discharge chamber is simulated using the finite-element method (FEM) solver COMSOL Multiphysics based on the mixture-averaged diffusion-drift theory of gas discharges and Maxwellian electron energy distribution function. A unique III-antimonide high-Ohmic semi-insulating aluminum gallium antimonide (AlGaSb) with finely digitated electron emission surface is modeled as planar cathode electrode coupled to ITO/SiO2 planar anode electrode across a gas discharge gap of 100 µm distance. Argon (Ar) and argon mixed with a mole fraction of 5% hydrogen (Ar/H2) gas medium are seperately introduced into the micro gap at sub-atmospheric pressure of 150 Torr, and the cell is driven at 1.0 kV DC by a stationary power source to simulate the transitions from electron field emission state toward self-sustained normal glow discharge state. The model is simulated to exhibit the transient physical characteristics of the AlGaSb-Ar/H2 glow-discharge micro plasma system by solving the spatio-temporal dynamics of various discharge parameters, including electron density, electron energy density, electron current density and electric potential. It has been observed that a fraction of hydrogen addition to argon can be used as an effective tool in modeling application-specific hybrid micro plasma – semiconductor based infrared photodetector devices.
Keywords: Malzeme Fiziği; Air-Space Transportation; Material Physics; Kompozit ve Hibrit Malzemeler; Microplasma; AlGaSb; DC plasma simulation; infrared photodetector.; Mikroplazma; AlGaSb; DC plazma simülasyon; kızılötesi fotodetektör; Hava-Uzay Ulaşımı; Composite and Hybrid Materials; Micro and Nanosystems; Mikro ve Nanosistemler